Skin conditions in the athlete - Pecci, M.; Comeau, D.; Chawla, V. (The American Journal of Sports Medicine, 2009)
Dermatologic conditions are a common presenting complaint in the athletic training room. There are many different causes for rashes, and treatment options vary depending on the condition and the severity. Bacterial infections of the skin have a variety of different appearances and can spread rapidly among individuals. Healthcare providers need to be aware of the increasing prevalence of methicillin-resistant Staphylococcus aureus when making the choice of antibiotics. Other infectious rashes, including tinea and herpes, are well-described conditions in wrestlers; however, these rashes can be seen in any athlete, especially those engaged in contact sports. Early recognition and appropriate treatment are important to clear the rash and reduce the spread to others. In addition to infectious rashes, athletes are prone to mechanical rashes and skin conditions due to friction and tight-fitting equipment. Sports medicine providers must not only diagnose and treat these conditions but also be aware of the return-to-play guidelines set forth by the governing bodies under which he or she operates.